APLIKASI TRICHOKOMPOS LIMBAH ECENG GONDOK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PAKCOY (Brassica rapa - Charles Charles; Fetmi Silvina; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of giving trichokompos waste water hyacinth and to get the best dose on the growth and production of pakcoy. This study was conducted experimentally using a completely randomized design. The treatment in this research is dosage of trichokompos waste water hyacinth which consist of 5 levels were : 0 kg.ha-1(T0),1,5 kg.ha-1(T1), 2 kg.ha-1(T2),2,5 kg.ha-1(T3), and 3 kg.ha-1(T4). The observed data were analyzed statistically using analyzed of varian and tasted further by DUNCAN’S new multiple range test of 5%. The result of this research indicate that giving of trichokompos waste water hyacinth can increase the growth and production of pakcoy. The giving of trichokompos waste water hyacinth dose 3 kg per plot produces pakcoy’s best growth and production.Keywords: pakcoy, Trichokompos, waste eceng gondok